Persistent gap in menopause care 20 years after the WHI: a population-based study of menopause-related symptoms and their management. (December 2022) - Trémollieres, Florence A.; André, Gabriel; Letombe, Brigitte; Barthélemy, Luc; Pichard, Amélie; Gelas, Bertrand; Lopès, Patrice
Highlights: This population-based survey of 5004 French women confirms the high frequency of climacteric symptoms as well as of genitourinary syndrome of menopause (GSM) in the first 15 years of menopause. The impact of climacteric/GSM symptoms on quality of life appeared significant, with 25 % of the women aged 55–59 years rating their quality of life between 8 and 10 on a 10-point visual analogic scale. About 44 % of the surveyed women never discussed their climacteric/GSM symptoms with their health care provider. Only, 6 % of the women were taking menopause hormone treatment (MHT) at the time of the survey. The main reasons for not using MHT were fear of hormones and of MHT side-effects. 62 % of the women reported that the decision not to take MHT was supported by their physician. Abstract: Objectives: To assess the current management of menopause in France with regard to menopause-related and genitourinary symptoms, with a focus on use of menopause hormone therapy (MHT). Design, setting, and participants: The ELISA Study is a population-based survey of 5004 French representative women aged 50 to 65 years. From July to August 2020, the participating women answered an online computer-assisted web interview on menopause-related and genitourinary symptoms and their management, including use of MHT. Main outcomes and measures: Prevalence of menopause-related and genitourinary symptoms in postmenopausal women. Management of these symptoms, including the reasons for not doing so, management by health care providers, and use of MHT. Results: Among the 5004 selected women, 4041 whose postmenopausal status was confirmed were included in the final analyses. Of the untreated 3685 women, 87 % reported at least 1 menopausal symptom, with a significantly higher percentage of symptomatic women in the 50–54 age group (92 %, p < 0.05) than in the other two age groups (55–59 years: 89 % and 60–64 years: 82 %). 68 % of the surveyed women experienced on average 2.5 symptoms of the genitourinary syndrome of menopause (GSM). Using a visual analogue scale (VAS) from 0 (no impact) to 10 (high impact) to evaluate the impact of menopausal/GSM symptoms on their quality of life, mean VAS score was 5.9 (SD: 2.2), with 25 % of the women aged 55–59 years rating their quality of life between 8 and 10. 61 % of the surveyed women reported being regularly followed by a health care professional. 44 % of women reported never having discussed their menopausal/GSM symptoms with a health care provider. The main reasons were because menopause is "a normal part of women's lives", because it was not "necessary to do so", or their symptoms were "not serious enough". Only 242 women (6 %) were current MHT users, of whom 49 % were using estrogen-alone therapy and 71 % were using transdermal estrogens. Fear of hormones (35 %) and MHT side-effects (25 %) were the main reasons given for not using MHT. 62 % of the women reported that the decision not to take MHT was supported by their physician. Conclusions and relevance: This large population-based survey confirmed not only the high prevalence of menopause-related and GSM symptoms in postmenopausal women within the first 10–15 years after menopause, but also the very low percentage of MHT users in France. Twenty years after the publication of the initial Women's Health Initiative (WHI) results, management of postmenopausal women is still characterized by unmet needs in menopausal care. Therefore, there is a strong need to educate the public and health care providers about menopause-related problems and possible solutions, including MHT, through dedicated educational programs.